Factor of influence of baseline data on the realization of integrated territorial development in the Arctic conditions - Bidov Tembot; Khubaev Alan; Lotkin Victor; Borovkova Anastasia (BIO Web of Conferences)
This article analyzes the influence of input data on the process of implementation of integrated territorial development in the Arctic conditions. The study is based on the analysis of data obtained from various sources such as statistical reports, geographical maps, sociological surveys and others. This study examines the factors affecting the construction processes of complex territorial development, in particular, the application of work organization project in the Arctic conditions. The implementation of the project and factors affecting the project implementation are also analyzed. The results of the study make it possible to identify the key factors affecting the success of territory development programs in the Arctic conditions and offer recommendations to improve the quality of input data used in the planning and implementation of integrated territory development projects. Based on the results obtained, the interrelationships of technological processes by various parameters are revealed, which in turn will allow us to determine the presence and levels of influence of the assumed factors on the changes in the implementation of the processes of integrated territorial development in the Arctic conditions.